Good Corporate Governance (GCG) and Corporate Value : The Mediating Role of Return on Equity in The Banking Sector - Agus Zul Bay; Fitri Kumalasari (Politeknik Baubau, 2025)
This study is important as it provides insights for investors and stakeholders in understanding how aspects of Good Corporate Governance (GCG) influence firm value, both directly and indirectly, with Return on Equity (ROE) as a mediating variable. The study examines the impact of four GCG aspects on firm value, with ROE serving as the mediating variable. A sample of 13 banking sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022 was selected using purposive sampling. To evaluate the mediation effect, panel data regression analysis and the Sobel test were employed. The results of Structural Model I indicate that the board of directors does not have a significant effect on ROE, while institutional ownership, independent commissioners, and managerial ownership show significant impacts. The simultaneous test confirms that the independent variables collectively and significantly influence ROE. The results of Structural Model II reveal that institutional ownership, managerial ownership, and ROE significantly affect firm value (PBV), whereas independent commissioners and the board of directors do not have a significant impact. The simultaneous test further confirms that PBV is significantly influenced by the independent variables collectively. According to the Sobel test results, ROE does not function as a mediating variable in the relationship between the independent variables and PBV.